2023
DOI: 10.1021/acsomega.2c07905
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Ginger Waste-Derived Biochar for Simultaneous Multiclass Antibiotics Remediation in Aqueous Medium

Abstract: The presence of antibiotics in the aqueous environment has been a serious concern primarily due to the development of antimicrobial resistance (AMR) in diverse microbial populations. To overcome the rising AMR concerns, antibiotic decontamination of the environmental matrices may play a vital role. The present study investigates the use of zinc-activated ginger-waste derived biochar for the removal of six antibiotics belonging to three different classes, viz., β-lactams, fluoroquinolones, and tetracyclines fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…It was also instrumental in the generation of 1 O 2 during PDS decomposition. Consistent with previous studies, the signal intensities of the characteristic peaks associated with C=O (1615 cm −1 ) and C-O (1020 cm −1 ) were substantially reduced in the TSBC used [51,55]. This observation suggested the active participation of O-containing groups in TSBC in facilitating the PDS activation process for SMX degradation.…”
Section: Identification In the Active Sitessupporting
confidence: 90%
“…It was also instrumental in the generation of 1 O 2 during PDS decomposition. Consistent with previous studies, the signal intensities of the characteristic peaks associated with C=O (1615 cm −1 ) and C-O (1020 cm −1 ) were substantially reduced in the TSBC used [51,55]. This observation suggested the active participation of O-containing groups in TSBC in facilitating the PDS activation process for SMX degradation.…”
Section: Identification In the Active Sitessupporting
confidence: 90%
“…Furthermore, at pH 6.0–7.0, the surface of Fe/Zn-biochar was negatively charged, while tetracycline was in a neutral form, resulting in the lowest electrostatic repulsion and the highest adsorption capacity . Meghani et al demonstrated that the zinc-activated ginger-waste biochar showed high adsorption capacities, effectively removing oxacillin, ciprofloxacin, enrofloxacin, chlortetracycline, and doxycycline from the aqueous, with a removal efficiency of more than 95%. This is attributed to ZnCl 2 , a Lewis acid, serving as a dehydration agent during pyrolysis, promoting an increased surface area and biomass porosity of biochar.…”
Section: Factors Influencing Antibiotics Removal By Biocharmentioning
confidence: 99%